Theatre in Towns - Nicholson, Helen (Taylor & Francis, 2023)
Theatre in Towns offers a contemporary perspective on the role of theatre in the cultural life of towns in England. Exploring volunteer-led, professional and community theatres, this book investigates the rich and diverse ways that theatres in towns serve their locality, negotiate their civic role, participate in networks of mutual aid and exchange, and connect audiences beyond their geographical borders. With a geographical focus on post-industrial, seaside, commuter and market towns in England, the book opens questions about how theatre shapes the narratives of town life, and how localism, networks and partnerships across and between towns contribute to living sustainably. Each chapter is critically and historically informed, drawing on original research in towns, including visits to performances and many conversations with townspeople, from theatre-makers, performers, set-builders, front-of-house volunteers, to audience members and civic leaders. Theatre in Towns asks urgent questions about how the relationships between towns and theatres can be redefined in new and equitable ways in the future. Theatre in Towns brings new research to scholars and students of theatre studies, cultural geography, cultural and social policy and political sociology. It will also interest artists, policy-makers and researchers wanting to develop their own and others' understanding of the value of active theatre cultures in towns.